PLAYERUNKNOWN’S BATTLEGROUNDS: YET ANOTHER INTERNET GAMING ADDICTION - Al-Qahtani, Arwa Ahmed; Alenzi, Abdulkarem Awad S; Shoukat Ali, Akbar (Journal of Ayub Medical College Abbottabad, 2020)
The overarching goal of the video games is to amuse the end-users by means of interactive systems that are now existent across numerous platforms such as personal computer, mobile phones, tablets and game consoles. PlayerUnknown’s Battlegrounds (PUBG) is a multiplayer online game. The addiction of PUBG is soaring worldwide and it has thick user-base. It is suggested that inhuman attitudes such as lack of empathy and war-related sentiments are likely to emerge among children who play aggressive and violent games like PUBG. In 2018, World Health Organisation (WHO) acknowledged online gaming compulsion as a grave mental health problem. Some of the well-known repercussions of playing PUBG video game are eyes strain, exhaustion, headache, obesity, poor quality of sleep, insomnia, withdrawal symptoms (rage and irritability) and even drug abuse owing to compulsive disorder. This game craze is unfortunately triggering world’s young population to invest their valuable time, money and effort in a no-return business, and therefore needs urgent measures. The overarching goal of video games is to amuse the end-users by means of interactive systems that are now existent across numerous platforms such as personal computer, mobile phones, tablets and game consoles. Player Unknown’s Battlegrounds (PUBG) is a multiplayer online game. The addiction of PUBG is soaring worldwide and it has thick user-base. It is suggested that inhuman attitudes such as lack of empathy and war-related sentiments are likely to emerge among children who play aggressive and violent games like PUBG. In 2018, World Health Organisation (WHO) acknowledged online gaming compulsion as a grave mental health problem. Some of the well-known repercussions of playing PUBG video game are eyes strain, exhaustion, headache, obesity, poor quality of sleep, insomnia, withdrawal symptoms (rage and irritability) and even drug abuse owing to compulsive disorder. This game craze is unfortunately triggering world’s young population to invest their valuable time, money and effort in a no-return business, and therefore needs urgent measures. Keywords: Internet Gaming Disorder; Mental Health; Player Unknown’s Battlegrounds (PUBG)